2020
DOI: 10.1021/acssuschemeng.9b07726
|View full text |Cite
|
Sign up to set email alerts
|

Structural Disorganization and Chain Aggregation of High-Amylose Starch in Different Chloride Salt Solutions

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 59 publications
2
17
1
Order By: Relevance
“…4(c). Native RMS had X c = 21.9 ± 0.3% and HAMS had X c =12.9 ± 0.5%, similar to the data reported elsewhere (Chen et al, 2017a;Liu et al, 2019;Li et al, 2020). The modified RMS and HAMS samples followed similar trends of variation in X c .…”
Section: Morphology Of Modified Rms and Hamssupporting
confidence: 86%
See 1 more Smart Citation
“…4(c). Native RMS had X c = 21.9 ± 0.3% and HAMS had X c =12.9 ± 0.5%, similar to the data reported elsewhere (Chen et al, 2017a;Liu et al, 2019;Li et al, 2020). The modified RMS and HAMS samples followed similar trends of variation in X c .…”
Section: Morphology Of Modified Rms and Hamssupporting
confidence: 86%
“…) is an important parameter reflecting the molecular size or mass of a polymer in a given solvent at a certain temperature. Thus, it can be used to evaluate the influence of hydrolysis time on starch (Trinh & Dang, 2019;Li et al, 2020). Fig.…”
Section: Intrinsic Viscosity ([η]mentioning
confidence: 99%
“…The high concentration of the CaCl 2 solution is essential for the preparation of such a starch material. The lowest salt concentration to disorganize G80 starch granules is 31% . If the concentration is lower than that, a transparent mixture cannot be formed and even a film cannot be formed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, we and other researchers have found that some salt ions (e.g., Zn 2+ and Ca 2+ ) can not only disorganize and amorphize starch granules effectively but also reinforce the starch chain network by forming amylose–metal cation inclusion complexes. Because these salt ions are hygroscopic and can combine with water to form hydrates easily, polymer materials containing them could have improved water-holding capacity . Moreover, these salt ions can impart the materials with electrical conductivity.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation